Managing Diversity in the Chinese Organizational Context: The Impact of Workforce Diversity Management on Employee Job Performance - Li, Zhiwen; Oljaca, Marijana; Firdousi, Saba Fazal; Akram, Umair (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the impact of workforce diversity management on employee job performance in the Chinese organizational context, considering the mediating effect of person-job match and employee commitment and the moderating effect of structural empowerment. Data were collected from 400 telecommunication sector employees in China. All hypotheses were tested through structural equation modeling (SEM). The findings of the study illustrated that workforce diversity management has a positive and significant impact on employee job performance. Furthermore, the results indicated that person-job match and employee commitment partially mediate the relationship between workforce diversity management and employee job performance. Moreover, structural empowerment directly affects employee job performance, whereas a moderating effect is also found in the relationship between workforce diversity management and employee job performance. Finally, implications and limitations are discussed.